Recognizing Racism in US Bioethics as the Subject of Bioethical Concern - Galarneau, Charlene (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Attending to racism and US bioethics raises the question of whether and how racism in bioethics has been the subject of bioethical scrutiny. Bioethics has certainly brought its analytical tools to bear on racist aspects of clinical care and biomedical research. But has bioethics studied racism in bioethics as its subject? A close examination of relevant reports, articles, and books in the US bioethics literature published in the early days of the field, pre-2000, shows mixed findings. In the 1970s, racism as a bioethical concern was variously nonexistent, vaguely implied, and powerfully examined and condemned. In the late 1980s/early to mid-1990s, racism was more frequently described and critiqued, often in the context of discussions about African American perspectives of biomedical ethics and inequities in health care. Understanding how racism in bioethics has been addressed as an ethical concern has consequences for the historical narratives told about the field, for antiracist bioethics work today, and for envisioning an antiracist future for bioethics.